Behavioral response of mule deer to natural gas development in the Piceance Basin - Northrup, Joseph M., author; Wittemyer, George, advisor; Anderson, Charles R., Jr., committee member; Hobbs, N. Thompson, committee member; Hooten, Mevin B., committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.